2019
DOI: 10.1155/2019/3051945
|View full text |Cite
|
Sign up to set email alerts
|

Severe Drug-Induced Liver Injury from Combination Encorafenib/Binimetinib

Abstract: Encorafenib/binimetinib is a new combination BRAF/MEK inhibitor used in the treatment of advanced or metastatic BRAFV600-mutant melanoma. Though generally tolerated well, mild to moderate aminotransferase elevations are common. However, significant liver injury has not been demonstrated in the literature. Here, we report the first case of severe hepatic injury associated with encorafenib/binimetinib in a 58-year-old gentleman requiring admission and extensive workup. He was successfully treated by withdrawing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…MEK inhibitors did not potently inhibit BSEP (Table 1) but showed clinical adverse effects of liver toxicity (Welsh and Corrie, 2015). The severity of liver injury increases when two inhibitors targeting the RAS/RAF/EMK/ERK pathway are combined (Gravbrot and Sundararajan, 2019). These results suggested that CYP7A1 induction could be a culprit for hepatotoxicity, independent of BSEP inhibition, and potentially explain the clinical observations for this class of drugs (Verzijl et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…MEK inhibitors did not potently inhibit BSEP (Table 1) but showed clinical adverse effects of liver toxicity (Welsh and Corrie, 2015). The severity of liver injury increases when two inhibitors targeting the RAS/RAF/EMK/ERK pathway are combined (Gravbrot and Sundararajan, 2019). These results suggested that CYP7A1 induction could be a culprit for hepatotoxicity, independent of BSEP inhibition, and potentially explain the clinical observations for this class of drugs (Verzijl et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Binimetinib is a selective and orally available MEK1/2 inhibitor . Binimetinib in combination with encorafenib was developed for treating adult patients with unresectable or metastatic melanoma. , A recent report indicated that combination of encorafenib and binimetinib caused rare but severe liver injury . However, the mechanistic basis of the liver injury is unclear.…”
Section: Introductionmentioning
confidence: 99%